Factors Regulating Plasma Protein Synthesis - Bocci, V; Pacini, A (Thrombosis and Haemostasis, 1973)
The intravenous injection of a large amount of homologous fibrinogen in the rabbit produces typical changes in the level of circulating fibrinogen. The first peak is due to the administered fibrinogen while the second, occurring after 16 hr, is interpreted as being due to the stimulation of hepatic synthesis and release of preformed fibrinogen. This typical profile was obtained with different fibrinogen preparations but not with heterologous fibrinogen. Neither was it obtained after administration of homologous γ-globulin, α-globulin or albumin. Assuming that enhancement of hepatic synthesis might be due to fibrinogenolytic products, the effect of the injection of fibrinogen digest products (FDP) was investigated. Administration of homologous FDP causes, within 24 hours, a significant increase of the plasma fibrinogen level. The critical requirement of injecting either the protein solution or saline intravenously rather than subcutaneously is emphasized. In conclusion, FDP appear to be endowed with the novel property of stimulating fibrinogen synthesis and possibly of causing the release of preformed fibrinogen.